Use of low-dose sulodexide in IgA nephropathy patients on renin-angiotensin system blockades - Byeong Yun Yang; Hee Seon Lee; Sang Heon Song; Ihm Soo Kwak; Soo Bong Lee; Dong Won Lee; Eun Young Seong (The Korean Society of Nephrology, 2012)
Background: Despite using renin-angiotensin system (RAS) blockades, some of the patients with immunoglobulin A (IgA) nephropathy often had persistent proteinuria of more than 500 mg/d. They need to be managed further by alternative methods to halt the progression of the disease; these methods could also be applied safely over a long period of time. In this context, sulodexide has been studied for the management of diabetic nephropathy. Methods: A retrospective review was carried out involving 20 patients with IgA nephropathy who had been taking sulodexide (50 mg daily) as an add-on therapy together with an optimal dose of RAS blockades during 2008-2009. We evaluated the proteinuria reduction rates and renal function changes. Results: During 11.1±72.7 months of follow-up duration, urinary protein-to-creatinine ratio (UPCR) decreased for 1.57±0.6 to 1.17±0.7 g/g (P=0.032). Twenty-five percent of the patients showed a greater than 50% reduction of UPCR, and 40% had a UPCR of less than 1.0 g/g at their final observations. The analysis of the factors contributing to the effect found that a higher pretreatment UPCR showed a significant correlation with the UPCR decrease (r=0.45, P=0.047). Neither the adverse effects nor the renal function impairments were documented during the management. Conclusion: Low-dose sulodexide has an additional modest antiproteinuric effect on IgA nephropathy undergoing RAS blockade therapy.